Literary Lessons in Law: Legal Culture in a Changing Welfare State - Blomquist, Helle (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
Can literary fiction provide a specifically advantageous framework for discussions about law and legal culture in an increasingly diverse society? This study addresses the challenges that some aspects of postmodernity pose to legal culture and legal thinking in the Danish welfare state. Showing how literature can take an open space in public debate I venture into an analysis of two Danish literary creations – the poem ‘The Coffee Break Team’ [Da: Kaffeholdet. My translation] from 2013 and a novel Pelle, The Conqueror, written 1907-10. As a third dimension a small sample of students is inquired about the poem. They are studying to become welfare state professionals and hence bearers of the relation between the state and its citizens. I discuss my literature samples against changes that have taken place in the Danish nation building project involving inclusion or exclusion of groups of the population. In a concluding section I balance my findings in relation to the initial question and place them within the law and literature tradition.